The Effect of Flipbook Media on Elementary School Students' Critical Thinking and Descriptive Writing Skills - Roviani, Wulan Sri; Samodra, Y. Touvan Juni; Halidjah, Siti; Priyadi, Antonius Totok; Karolina, Venny (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to analyze the effect of flipbook media on the critical thinking and descriptive writing skills of fifth-grade elementary school students. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research subjects were 48 fifth-grade students of SD Negeri 12 Sungai Kunyit, consisting of 24 students in the experimental class and 24 students in the control class. The experimental class received instruction using flipbook media, while the control class used conventional media. Data were collected through critical thinking tests, descriptive writing tests, observation sheets, and documentation. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene's homogeneity test, independent samples t-test, and Cohen's d effect size. The results showed a significant difference between the experimental and control classes in both critical thinking and descriptive writing skills, with a significance value of 0.000 < 0.05. The effect size was large for critical thinking (d = 1.12) and descriptive writing (d = 0.95). Therefore, flipbook media was proven effective in improving students' critical thinking and descriptive writing skills. This study concludes that flipbook media can be used as an innovative digital learning resource to support Indonesian language learning and higher-order thinking skills in elementary schools.